Enhancing Security of ATM Transactions via Debit Cards - Nath, Asoke; Saha, Sourya; Gupta, Sarthak; Das, Nilarghya (International Journal of Computer Sciences and Engineering, 2019)
Nowadays, there has been a sudden surge in thefts from ATMs. Though ATM cum debit cards provides us with a faster access to our money, there lies a big security issue with such cards. The cards are skimmed by using skimming devices and the information from these cards are often stolen when one tries to perform transactions at an ATM. This information is then misused by the people performing such thefts. This paper will shed light upon the above matter. In this paper, we will be discussing the very basics of an ATM cum debit card and an ATM. Then we will talk about the method in which such thefts take place which we can refer to as skimming. In addition to that, we will elaborate on a technique that could possibly be used to prevent such thefts from taking place. The paper will elaborate on the measures to be taken to implement such a mechanism and the scope of this mechanism.